Metode Mendidik Anak dalam Keluarga: Studi Kasus Pemenang Keluarga Sakinah Tingkat Nasional Tahun 2014 - Azizah, Rosyida Nur (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
Family is the smallest unit for children in society. Family is the most powerfulcharacter to build children in environment. The good family has been guided by theQuran and Al Hadith in educating their children.The family like that is often calledSakinah Family. Actually, Sakinah Family is the typical terminology in Indonesia thatdescribes the happy family in the perspective of Islam. Then in Indonesia, was held theselection of Sakinah Family Model, from the district level until national level. So it isexpected that Sakinah Family will be able to become a figure in the household and ableto become a benchmark in educating children. In 2014, the winner Sakinah Family of theNational Level is Mr K.H. Drs. Khariri Sofa, M.Ag’s Family from Banyumas. The methodused in educating children in Mr. Khariri’s family can be analogied as the process ofplanting tree. They are six conditions that should be fulfilled to do it in best result.